The Morphological Structures of Derived Forms in the Thirtieth Part of the Qur’an: A Morphological Study - Hussein, Sukna Jebur (Dzil Majaz: Journal of Arabic Literature, 2025)
This study addresses the linguistic problem of understanding Qur’anic expressions through their morphological structures, particularly in the thirtieth part (Juz ‘Amma) of the Holy Qur’an. Derivation (al-ishtiqāq) plays a crucial role in enriching Arabic vocabulary and revealing layers of meaning embedded in Qur’anic discourse. The research aims to examine the structures of derivatives found in selected verses, identify their linguistic functions, and clarify how these forms contribute to interpreting the intended meanings of the text. Employing a descriptive–analytical method, the study begins with a preamble outlining the origins of derivation in both linguistic and terminological perspectives, its importance in the development of Arabic, and its major types. The analysis involves classifying derivative forms and examining their semantic implications within Qur’anic contexts. The findings show that derivative analysis provides an effective interpretive tool across linguistic levels, enabling a deeper and more precise comprehension of Qur’anic meanings. All major derivative forms appear in the examined verses except the instrumental noun (ism al-ālah). The study also highlights the centrality of the lexical root, which constitutes the semantic core from which morphological patterns emerge, predominantly based on the triliteral root system (faʿala). This research contributes to Qur’anic linguistic studies by demonstrating how derivational structures enhance textual interpretation